Probiotics and Their Role in Decreasing Diarrhea Prevalence in the Elderly Population: A Comprehensive Meta-Analysis - Muliana, Devika; Mulia, Vera Dewi; Suardi, Hijra Novia; Puspita, Nanda Ayu; Suryawati, Suryawati (Malacca Pharmaceutics, 2024)
Diarrhea is an atypical state of the digestive system characterized by a soft or watery texture in bowel movements. Antibiotic-related diarrhea is common in the elderly due to extensive antibiotic use. Probiotics are vital microorganisms that support the intestinal flora and reduce bacterial colonization in the intestinal wall. This study aimed to assess the effectiveness, type, and dose of probiotics for diarrhea in the elderly. A systematic review with meta-analysis was conducted using PubMed, ScienceDirect, and Google Scholar. Seven records with a total of 2,087 participants were included. A quantitative analysis was carried out using Review Manager version 5 software. A meta-analysis was conducted to assess the frequency of diarrhea. The results showed that using probiotics significantly reduced the risk of antibiotic-related diarrhea 0.53 times compared to the placebo administration (OR 0.53; CI 95% 0.29 to 0.98; I2 = 70%). The type of probiotics frequently given was the genera of Lactobacillus, Bifidobacterium, and Streptococcus, with consumption durations varying from 3 days to a maximum of 4 weeks. The dose of probiotics ranged from a minimum of 1.0 × 10⁶ CFU to a maximum dose of 2 × 10¹⁰ CFU. To conclude, probiotic administration is more effective than placebo in reducing the risk of antibiotic-related diarrhea in the elderly.